Life threatening and serious dermatoses - Swinyer, Leonard J., 1940-; Kopf, Alfred W.; Malkinson, Frederick D.; American Academy of Dermatology; Institute for Dermatologic Communication and Education ([Evanston, Ill.] : American Academy of Dermatology, 1978)
(Critical) This program consists of color slides with a syllabus of diagnoses that graphically depict a wide range of skin disorders including autoimmune and metabolic diseases, tumors, and several viral infections. Although the topic is broader than can be presented in a brief program, the slides are of excellent quality and accurately portray the disease entities. The collection is lossely grouped together but the presentation suffers from the lack of a written or audio component. It is recommended for limited use by dermatologists who need resource photographic material for instructional purposes
Rating: Recommended
Review date: Aug. 1981
Reviewer: Association of American Medical Colleges (AAMC)
Learning method: Support
From the collection of Leonard J. Swinyer, Alfred W. Kopf, Frederick D. Malkinson
Keywords: Emergencies; Skin diseases